MENUJU BUKU SAKU YANG INFORMATIF DAN KOMUNIKATIF DAN WISATA WISATA KOTA BUKITTINGGI - MUHAMMAD IQBAL ASRIL, Ir. Drs. Heldi, M.Si., Ph.D., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
West Sumatera own assets of the heritage cultural relic Duch Colonial in Bukittinggi famous by Jam Gadang as a icon, the monument is the oldest clock tower in the world. Jam Gadang become main attraction tourism and main asset to escalate locally-generated revenue.Current development in the world of technology like internet globalization is unconvincingly information. Information of the media printing it had opportunities and key part as a media information in tourism development. Prospect of making pocket book Bukittinggi with communicative and informative is expected gave the contribution to people, traveling with happiness and top experiences.Design method of tourism guide pocket book Bukittinggi city is created through metaphor method and adjusted with SWOT analysis, the colletion of data is do it by interview, survey in fields and documentation data and relevant reviews.The tourism pocket book design of Bukittinggi city is created by with purpose main media with creative program used with design principal method, photo documentation, explained texts, colour, interested layout and unique. The Design is support with some of media like: sticker, poster, x-banner, bookmark, t-shirt, pin and key chain.Keyword : Book, Pocket Book, Informative, Communicative, Tourism,Bukittinggi